Case Visit Activity Report An. S Patients with Short Stature Pulmonary Tuberculosis Through Family Medicine Approach - Butar Butar, Ananda Josua Triagus Pahala; Sevilla , Paulina; Mosso, Justhina Ensly; Novendy, Novendy (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Tuberculosis can occur in all age groups adults and children. Tuberculosis (TB) in children occurs in children aged 0-14 years and most common at ages 1-14 years. In the working area of the Cikupa Health Center, there are patients a daughter named An.S who was diagnosed with a new case of pulmonary tuberculosis and has stature short based on results plotting so that need done intervention through family doctor visit. Solving the problem pulmonary tuberculosis infection with short stature in An. S. A female patient, An.S , aged 2 years and 8 months, came with a complaint Cough with fever for 2 weeks. In addition, high growth was also obtained age-appropriate body The patient has received antibiotics and concoction but complaints do not improve. The patient's grandmother also had similar complaints. In this case, an intervention using a family medicine approach with Mandala of Health For get diagnosis holistic And done governance in a manner comprehensive. After the intervention of An.S showed improvement and is currently undergoing treatment. Height has increased from 84 cm to 86 cm also weight from 11.2 kg to 13 kg. The family has understood about TB disease and is willing to do screening and implement PHBS. Known sources of tuberculosis infection in An. S suspected of coming from the patient's grandmother. TB infection experienced by patients has an impact on inhibiting the patient's growth so that the patient's height does not increase. After comprehensive treatment and education, the patient's family understands tuberculosis, disease transmission and prevention so that it is hoped that the treatment will be carried out completely and can catch up with age-appropriate growth.